2001
DOI: 10.1289/ehp.01109605
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of memory and learning in older adults exposed to polychlorinated biphenyls via consumption of Great Lakes fish.

Abstract: An association between in utero polychlorinated biphenyl (PCB) exposure and impaired childhood intellectual functioning has been reported, but the potential impact of PCB exposure during adulthood on intellectual functioning has received little attention. We assessed the impact of PCBs and other fish-borne contaminants on intellectual functioning in older adults. The subjects were 49- to 86-year-old Michigan residents recruited from an existing cohort. Fish eaters ate > 24 lb of sport-caught Lake Michigan fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
85
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(104 citation statements)
references
References 24 publications
17
85
2
Order By: Relevance
“…The CNS involvement related to the hippocampus as memory and learning, but not cortical domains, was emphasized by several animal and epidemiological studies. [12][13][14][15][16] The deficits in attention and learning abilities show that PCB/PCDF neurotoxins can interfere with the integrity of short-term memory recalls, as in the present study. These results suggested that different neurotoxin might have a specific or different neurocognitive influence.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The CNS involvement related to the hippocampus as memory and learning, but not cortical domains, was emphasized by several animal and epidemiological studies. [12][13][14][15][16] The deficits in attention and learning abilities show that PCB/PCDF neurotoxins can interfere with the integrity of short-term memory recalls, as in the present study. These results suggested that different neurotoxin might have a specific or different neurocognitive influence.…”
Section: Discussionsupporting
confidence: 67%
“…Schantz et al reported an existing cohort in 2001 of adult sport-caught fish-eaters exposed to PCB who had impaired memory and learning. 15 The results of that study were similar to the results in Taiwanese adults, with cognitive decline limited to memory and learning ability, but not relevant to executive or sensory functions. 16 Experimental studies have shown that PCB have effects on the cortical and subcortical brain.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, Grandjean et al (31) studied the population of the Faroe Islands, who also eat a lot of fish, and reported significant decrements of IQ and abnormalities of behavior in children that increase with exposure levels. We have some evidence that adults who eat a significant amount of contaminated fish suffer from some cognitive deficits, attributed in different regions to methyl mercury by Mergler et al (32) and to PCBs by Schantz et al (33). One major question is whether it is the methyl mercury or the PCBs, both of which are present in most situations, that cause these effects, or whether perhaps it is the combination of the two.…”
Section: Neurobehavioral Abnormalitiesmentioning
confidence: 96%
“…To our knowledge, no study has specifically evaluated breast cancer risk in consumers of diets potentially high in PCBs, DDT/DDE, and PBDEs such as consumers of high amounts of sport-caught fish, anglers, families who operate charter fishing boats, or native populations, although several other health parameters, including fecundability (Buck et al 2000;McGuinness et al 2001), birth size (Fein et al 1984), puberty growth (Gladen et al 2000), and cognitive functioning (Jacobson et al 1990;Schantz et al 2001), have been investigated in these adult subpopulations as well as in children.…”
Section: Discussionmentioning
confidence: 99%